Human sexuality, family planning, and responsible parenthood - Sanchez, Custodiosa A.; Sanchez, Rey A. (Mandaluyong City, 2004)
The book starts from the study of man's nature and project of existence; the biological bases of human behavior patterns and their risks, family planning and responsible parenthood. The authors believe that this will help supply practical knowledge and understanding necessary for man's pursuit of well-being, happiness, intellectual and spiritual fulfillment. There are of course, many ways of treating and presenting the subject matter but the authors feel that this approach will be more appropriate and comprehensible to students who have no or little knowledge of the subject matter.
Keywords: Family planning; Human sexuality; Responsible parenthood